KONSTRUKSI SEPADAN DAN TAK SEPADAN ANTARA LARIK SAMPIRAN DAN LARIK ISI SEBUAH PANTUN - Hidayatul Astar (﻿Kantor Bahasa Provinsi Bangka Belitung, 2020)
Pantun merupakan salah satu puisi lama Melayu yang memiliki ciri keindahan atau keteraturan bahasanya. Banyak tulisan yang telah membahas hal tersebut, tetapi belum ada yang membahas secara lebih spesifik dari sisi konstruksi sepadan dan tak sepadan antara larik sampiran pertama (S-1) dan isi pertama (I-1) dan antara larik sampiran kedua (S-2) dan isi kedua (I-2). Metode yang digunakan adalah deskriptif kualitatif. Konsepsi tentang linguistik struktural hubungan sintagmatik yang dikemukan Robins (1992) dan konsepsi Alwi et.al. (2017) tentang unsur kalimat, fungsi sintaksis, susunan unsur, dan jenis kalimat menjadi acuan analisis data. Hasil penelitian menunjukkan bahwa ada tiga bentuk konstruksi pantun. Dari 100 pantun yang diteliti, 39 pantun atau 39% berkonstruksi sepadan penuh, 41 atau 41% berkonstruksi sepadan sebagian, dan 20 atau 20% berkonstruksi tak sepadan. Ketiga kategori konstruksi tersebut ditandai oleh ciri-ciri tertentu. Pantun kategori pertama ditandai oleh jumlah unsur, jumlah kata, fungsi sintaksis, susunan unsur, dan jenis kalimat yang sama; pantun kategori kedua ditandai oleh kesamaan dan ketaksamaan kelima aspek tersebut; pantun kategori ketiga ditandai oleh jumlah unsur dan fungsi sintaksis yang tak sama dan susunan unsur dan jenis kalimat yang sama dan tak sama. Pantun berkonstruksi sepadan lebih indah atau lebih teratur bahasanya daripada yang tak sepadan dan dapat menjadi acuan ketika berpantun. Pantun is one of the old Malay poems which has a characteristic of regularity of language. The beauty of pantun language has been discussed in many writings, but no one has discussed more specifically in term of its construction. This article discusses the form construction between the first sampiran lines (S-1) and the first content (I-1) and between the second sampiran lines (S-2) and the second content (I-2) of a pantun. The method used is descriptive qualitative method. A reference for data analysis is followed the conception of structural linguistics of syntagmatic relations proposed by Robins (1992) and Alwi et.al. (2017) specially syntactic elements, syntactic functions, sequence of elements, and type of sentence. The results of this study to show that there are three construction of pantun. Out of 100 pantun studied, 39 or 39% had full commensurate construction, 41 or 41% had partially commensurate construction, and 20 or 20% had incommensurate construction. All three construction kategories are marked by certain charecteristics. The first pantun kategories is characterized by the number of elements, number of words, syntactic functions, sequence of elements, and type of sentence of the same. The second pantun kategories is characterized by all five aspects of the same and not.The third pantun kategories is characterized by the number of elements and syntactic functions that are not the same and the sequence of elements and type of sentence of the same and not. Pantuns with commensurate constructions are more beautiful than pantuns that incommensurate and can be reference.